Application and development of the method of geodynamic zoning for forecasting the geodynamical danger at coal mines of China - Tianwei Lan; Hongwei Zhang; Sheng Li; A. S. Batugin; Weiguo Zhao; Qiang Li; Sujan Sun (Известия высших учебных заведений: Геология и разведка, 2019)
The method of geodynamic zoning experienced in China three periods of its development: «formation», «development», and «innovation». With the help of this method, the models were created linking the block structures of the crustal tectonic plates and coal minefields. A program for calculating the stress state of the rocks massif was developed, taking into account the data on geodynamic zoning. A model of multifactorial recognition and forecasting of the geodynamical danger was developed. The realization of the geodynamical danger in minefields is assumed to demand elaboration of the special conditions in the bearing massif, that's why the indexes and methods for the estimation of these conditions were determined. For the investigations of the connection between the energy of a rock burst and the size of the massif area involved in this process, the corresponding model was created and the conditions of the outbursts were determined. The effectiveness of the method of the recognizing the areas of the increased geodynamic danger was provided with the examples of the particular mines. For the Yue Jin and Jingxi minefields, the outbursts and rockbursts dangerous, threatened, and non-dangerous areas were identified. The application of the preventive measures for the increasing the geodynamic safety in mining is reccomended to have to be based on the results of the forecast.